In vitro release studies of furosemide reference tablets: influence of agitation rate, USP apparatus and dissolution media - Raúl Medina-López; Sergio Guillén-Moedano; Marcela Hurtado (International Association of Physical Chemists (IAPC), 2020)
Furosemide is a diuretic drug widely used in chronic renal failure. The drug has low solubility and permeability, which cause clinical problems. Studying the in vitro release performance elucidates the rate and extent of drug dissolved from dosage forms under different conditions. Furosemide reference tablets were tested using USP Apparatuses 1 and 2 as well as the flow-through cell method (USP Apparatus 4), a dissolution apparatus that simulates the human gastrointestinal tract better than the other methods. Dissolution profiles were created with USP Apparatuses 1 and 2 at 25, 50, and 75 rpm and 900 mL of 0.1 M hydrochloric acid, acetate buffer (pH 4.5), and phosphate buffer (pH 6.8). USP Apparatus 4 with a laminar flow of 16 mL/min and 22.6 mm cells was used. Drug dissolution was quantified at 274 nm for 60 min. Mean dissolution time, dissolution efficiency, time to 50 % dissolution, and time to 80 % dissolution data were used to compare dissolution profiles. Additionally, zero-order, first-order, Higuchi, Hixson-Crowell, Makoid-Banakar, and Weibull models were used to adjust furosemide dissolution data. Between USP Apparatus 1 and 2, significant differences were observed in almost all parameters at 50 and 75 rpm (p < 0.05). A similar dissolution profile (f2 > 50) with a pharmacopoeial dissolution method (USP Apparatus 2 at 50 rpm and 900 mL of phosphate buffer pH 5.8) and USP Apparatus 4 (laminar flow of 16 mL/min, 22.6 mm cells, and pH 6.8) was observed. The Weibull function was the best mathematical model to describe the in vitro release performance of furosemide in the three USP dissolution apparatuses. These results could be used to manufacture better furosemide dosage forms and decrease the negative clinical impact of current furosemide formulations.